Natural Disasters, Self-Insurance and Human Capital Investment : Evidence from Bangladesh, Ethiopia and Malawi - Yamauchi, Futoshi; Yohannes, Yisehac; Quisumbing, Agnes (2012)
This paper examines the impacts of disasters on dynamic human capital production using panel data from Bangladesh, Ethiopia, and Malawi. The empirical results show that the accumulation of biological human capital prior to disasters helps children maintain investments in the post-disaster period. Biological human capital formed in early childhood (long-term nutritional status) plays a role of insurance with resilience to disasters by protecting schooling investment and outcomes, although disasters have negative impacts on investment. In Bangladesh, children with more biological human capital are less affected by the adverse effects of floods, and the rate of investment increases with the initial human capital stock in the post-disaster recovery process. In Ethiopia and Malawi, where droughts are rather frequent, exposure to highly frequent droughts in some cases reduces schooling investment but the negative impacts are larger among children embodying less biological human capital. Asset holdings prior to the disasters, especially the household's stock of intellectual human capital, also helps maintain schooling investments at least to the same degree as the stock of human capital accumulated in children prior to the disasters.